2020
DOI: 10.1186/s13020-020-0298-x
|View full text |Cite
|
Sign up to set email alerts
|

The chloroplasts genomic analyses of Rosa laevigata, R. rugosa and R. canina

Abstract: Background: Many species of the genus Rosa have been used as ornamental plants and traditional medicines. However, industrial development of roses is hampered due to highly divergent characteristics. Methods: We analyzed the chloroplast (cp) genomes of Rosa laevigata, R. rugosa and R. canina, including the repeat sequences, inverted-repeat (IR) contractions and expansions, and mutation sites. Results: The size of the cp genome of R. laevigata, R. rugosa and R. canina was between 156 333 bp and 156 533 bp, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 70 publications
(69 reference statements)
0
9
0
Order By: Relevance
“…The length of the LSC, SSC, and IRs varied in the range of 84,046–89,021 bp, 16,914–18,821 bp, and 23,902–25,914 bp, respectively. Chloroplast genome size variation among different species, or even within different individuals of the same species, which has been reported in other species, such as Camptotheca acuminata [ 48 , 49 ], Eucommia ulmoides [ 50 ], Rosa rugosa [ 51 53 ] and Calanthe davidii [ 54 ]. This, besides polyploidy of plant material, has been shown to be due to the expansion/contraction of IR [ 55 ].…”
Section: Discussionmentioning
confidence: 84%
“…The length of the LSC, SSC, and IRs varied in the range of 84,046–89,021 bp, 16,914–18,821 bp, and 23,902–25,914 bp, respectively. Chloroplast genome size variation among different species, or even within different individuals of the same species, which has been reported in other species, such as Camptotheca acuminata [ 48 , 49 ], Eucommia ulmoides [ 50 ], Rosa rugosa [ 51 53 ] and Calanthe davidii [ 54 ]. This, besides polyploidy of plant material, has been shown to be due to the expansion/contraction of IR [ 55 ].…”
Section: Discussionmentioning
confidence: 84%
“…The length of the LSC, SSC, and IRs varied in the range of 84,046-89,021 bp, 16,914-18,821 bp, and 23,902-25,914 bp, respectively. Chloroplast genome size variation among different species, or even within different individuals of the same species, which has been reported in other species, such as Camptotheca acuminate [48,49], Eucommia ulmoides [50], Rosa rugosa [51][52][53] and Calanthe davidii [54]. This, besides polyploidy of plant material, has been shown to be due to the expansion/contraction of IR [55].…”
Section: Discussionmentioning
confidence: 65%
“…Statistical analysis of the locations of all identi ed SSRs showed that the number of SSRs located in the LSC region, SSC region and IR regions were 44-52, 8-12 and 4-14, respectively. Furthermore, we found that these SSRs were mainly distributed in IGS (38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54), and some in the CDS region (9)(10)(11)(12) and introns (8)(9)(10)(11)(12). A/T (no C/G) is the only mononucleotide SSRs type in the six species (Figures 6A and 7), and the repeat units of the other ve SSRs were also mainly composed of A or T (Figures 6A and 7).…”
Section: Repeat Sequences Analysismentioning
confidence: 97%
“…Species diagnosis for most of the Kaempferia genus was conducted using the loci of psbA-trnH and petA-psbJ as DNA barcodes (Techaprasan et al, 2010). petA-psbJ can be used as a candidate fragment for DNA barcoding in phylogeny and species identification of other species, including those of the Rosa (Yin et al, 2020), Bupleurum (Xie et al, 2021), and Zingiber (Li et al, 2020c) genera, as well as the Papaveraceae (Liu et al, 2020) and Lauraceae (Jo et al, 2019) families. These hypervariable regions are suitable candidates for species identification and provide evolutionary information about Salix species.…”
Section: Comparative Genomic Analysismentioning
confidence: 99%